Improving the Quality of Coffee Beans and Branding of Coffee Products of Sekar Adji MSMEs Malang Through Inovokasi Program Grants - Noer Syamsiana, Ika; Datumaya Wahyudi Sumari, Arwin; Fiernaningsih, Nilawati; Nurwicaksana, Wahyu Aulia; Nafisah, Nihayatun; Findi, Putri; Anggraini Ningrum, Annisa; Ibrohim Farros, Ammar; Wildan Fikri, Mohammad (Universitas Ahmad Dahlan, 2025)
Background: Coffee is a key plantation commodity in Indonesia, with Gunung Kawi producing Robusta, Arabica, and Excelsa varieties. However, local farmers still rely on traditional drying methods and outdated marketing, affecting bean quality and sales. This community service program seeks to address these issues by introducing a 30 kg-capacity rotary dryer to meet the SNI 01-2907-2008 standard and by providing digital marketing training to enhance competitiveness. Contribution: This program significantly supports Sekar Adji MSMEs by introducing a rotary dryer that enables coffee drying to meet national quality standards. Combined with digital marketing training and improved packaging, it enhances product promotion and competitiveness in the digital market, ultimately boosting MSME revenue. Method: The program involves four main activities: manufacturing and training on the use of a 30 kg-capacity rotary dryer, providing digital marketing training to enhance social media and e-commerce use, redesigning coffee packaging for better appeal, and restructuring the MSME organization to improve adaptability and management efficiency. Results: The program introduced a 30 kg-capacity rotary dryer and digital marketing training. The dryer reduced moisture content to 11.5%, and product packaging was improved with five new designs. The program significantly increased marketing reach and MSME revenue. Digital platforms such as Instagram, Tokopedia, and TikTok Shop were utilized to expand online presence, and a new organizational structure enhanced business operation. Conclusion: Analysis of the results shows that the program positively impacted product quality and sales at Sekar Adji MSMEs, primarily by improving drying processes and enhancing digital marketing through targeted training.